2005
DOI: 10.1128/jcm.43.9.4492-4497.2005
|View full text |Cite
|
Sign up to set email alerts
|

Microbiologic Response to Treatment of Bacterial Vaginosis with Topical Clindamycin or Metronidazole

Abstract: To compare the frequencies, concentrations, and antimicrobial susceptibilities of vaginal microbes isolated from women with bacterial vaginosis (BV) before and after therapy, 119 nonpregnant women aged 18 to 45 with clinical and Gram stain evidence of BV were randomized to receive intravaginal clindamycin or metronidazole. Vaginal swabs were collected at baseline and 7 to 12 days, 35 to 45 days, and 70 to 90 days following therapy for quantitative vaginal culture. For the 99 women completing all four visits, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 28 publications
2
45
0
5
Order By: Relevance
“…Furthermore, studies using quantitative PCR have shown that women with BV have larger quantities of M. hominis and that these levels correlate with Gram stain criteria for BV (43). A decrease in Mycoplasma colonization in women with BV following treatment with either topical metronidazole or clindamycin was reported by Austin et al (105).…”
Section: Mycoplasma and Ureaplasmamentioning
confidence: 91%
“…Furthermore, studies using quantitative PCR have shown that women with BV have larger quantities of M. hominis and that these levels correlate with Gram stain criteria for BV (43). A decrease in Mycoplasma colonization in women with BV following treatment with either topical metronidazole or clindamycin was reported by Austin et al (105).…”
Section: Mycoplasma and Ureaplasmamentioning
confidence: 91%
“…Ключевыми элементами данной экосистемы являются вагинальный эпите-лий и вагинальная флора [4,14,15,16].…”
Section: обзор литературных данныхunclassified
“…Większość schematów terapeutycznych opiera się głównie na metronidazolu i klindamycynie oraz tinidazolu [20]. Największym problemem, jaki sprawia BV, jest niepowodzenie leczenia i skłon-ność do występowania nawrotów.…”
Section: Leczenieunclassified